Eniluracil blocks AREG signalling‐induced pro‐inflammatory fibroblasts of melanoma in heart failure - Qin Ran; Long Chen (ESC Heart Failure)
Abstract Aims Heart failure (HF) is characterized by a heightened risk of melanoma, which often metastasizes to the heart. The overlap pathology between HF and melanoma includes chronic low‐grade inflammation and dysregulation of inflammatory cancer‐associated fibroblasts (iCAFs). The impact of HF on iCAF‐driven tumour inflammation remains obscure. Methods and Results To identify critical genes for HF development, transcriptomic data (GSE57338) containing 313 clinical HF samples [136 healthy controls, 95 ischaemia (ISCH) and 82 dilated cardiomyopathy (DCM)] were analysed to screen differentially expressed genes (DEGs) and perform enrichment analysis. Fifty‐one DEGs in ISCH and 62 DEGs in DCM were identified with log2|fold change (FC)| ≥ 1 and P value ≤0.05. All these genes are involved in extracellular matrix organization, immune/inflammatory responses and Wnt signalling pathways. Then, the overall survival curves and prognostic models of DEGs in melanoma were evaluated. The correlation of gene expression with lymphocyte infiltration levels was assessed. Only aldehyde oxidase 1 (AOX1) and amphiregulin (AREG) maintained the same trend in melanoma as in HF, negatively affecting prognosis by regulating lymphocyte infiltration (log‐rank P value = 0.0017 and 0.0019). The potential drug molecules were screened, and the binding energies were calculated via molecular docking. Eniluracil, a known AOX1 targeting drug, was found to stably bind with AREG (hydrogen bond binding energies: −65.633, −63.592 and −62.813 kcal/mol). Conclusions The increased prevalence of melanoma in HF patients and its propensity for cardiac metastasis may be due to AREG‐mediated systemic low‐grade inflammation. Eniluracil holds promise as a therapeutic agent that may block AREG signalling, inhibiting the activation of iCAF mediated by regulatory T cell (Treg) and neutrophil.